1997
DOI: 10.1124/mol.51.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alteration of α2C-Adrenoceptor Expression in Mice: Influence on Locomotor, Hypothermic, and Neurochemical Effects of Dexmedetomidine, a Subtype-Nonselective α2-Adrenoceptor Agonist

Abstract: SUMMARY␣ 2 -Adrenergic receptors (␣ 2 -ARs) regulate many physiological functions and are targets for clinically important antihypertensive and anesthetic agents. Three human and mouse genes encoding ␣ 2 -AR subtypes (␣ 2A , ␣ 2B , and ␣ 2C ) have been cloned. We investigated the involvement of the ␣ 2C -AR in ␣ 2 -adrenergic pharmacology by applying molecular genetic techniques to alter the expression of ␣ 2C -AR in mice. The effects of dexmedetomidine, a subtype-nonselective ␣ 2 -AR agonist, on monoamine tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
98
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(107 citation statements)
references
References 27 publications
8
98
0
1
Order By: Relevance
“…21,25 Briefly, the ␣ 2C -AR gene was inactivated in 129/Sv embryonic stem cells 31 which were injected into C57BL/6J blastocysts, and the resulting chimeric mice were bred to F 1 (C57BL/6J × DBA/2J) animals. These animals were back-crossed for several generations to C57BL/6J mice; then intercrossed, and the tested ␣ 2C -KO mice were offspring of closely related F [11][12] pairs, which were combinations of mice with wild-type, heterozygous or homozygous genotypes for the ␣ 2C -AR mutation.…”
Section: Animalsmentioning
confidence: 99%
See 4 more Smart Citations
“…21,25 Briefly, the ␣ 2C -AR gene was inactivated in 129/Sv embryonic stem cells 31 which were injected into C57BL/6J blastocysts, and the resulting chimeric mice were bred to F 1 (C57BL/6J × DBA/2J) animals. These animals were back-crossed for several generations to C57BL/6J mice; then intercrossed, and the tested ␣ 2C -KO mice were offspring of closely related F [11][12] pairs, which were combinations of mice with wild-type, heterozygous or homozygous genotypes for the ␣ 2C -AR mutation.…”
Section: Animalsmentioning
confidence: 99%
“…[16][17][18][19][20] It has also been demonstrated that genetically altered ␣ 2C -AR expression in mice does not significantly change the potent inhibitory effect of ␣ 2 -AR agonists on brain monoamine turnover. 21 However, according to a recent study employing transgenic mice, ␣ 2C -AR may have a subtle modulatory effect on brain DA and 5-HT balance. 21 Furthermore, the ␣ 2C -AR gene mutations in mice have been associated with changes in aggressive behavior, the startle reflex and its prepulse inhibition, 22 damphetamine-stimulated locomotor activity, and l-5-hydroxytryptophan-induced behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations